Modifiable cardiovascular disease risk and its associated factors among 15-24 years aged in chapakot municipality Syangja. - Hamal, Arjun (2021)
SUMMARY: Cardiovascular disease is the disease of heart, Blood vessels, cerebrovascular disease such as ischemic heart disease, coronary heart disease, stroke etc. These conditions are the serious consequences of the CVDs. Hypertension, hyperlipidemia, high level blood cholesterol is the initial stage of the CVDs. Cause of CVDs is risk factor. There are known two types of risk factors ie. Non-modifiable and modifiable risk factors. Non-modifiable risk factors those that can't avoid and prevent . Modifiable risk factors are behavioral and lifestyle-related factors that can avoid or reduce by intervention. Therefore aim of this study is to determine the prevalence of CVDs modifiable risk factors and its associated factors among 15 to 24 years of age in Chapakot Municipality. This study was descriptive cross-sectional conducted in the semi-urban community of Chapakot Municipality, Syangja district. Total 206 (Male-80and Female-126)participants were involved in this study. Structured questionnaire contains demographic background tobacco-related behavior, alcohol consumption behavior, fruit/vegetable consumption behavior, salt consumption, physical exercise and anthropometric measurement and information were recorded. Data were entered in epi-data 3.1 and exported in SPSS 26 version for further cleaning and analysis. Frequency tables were used and percentage tables were calculated for univariate analysis. Likewise, Chi-square tests were analyzed to measure the association between CVDs risk factors and socio-demographic characteristics and the odds ratio was calculated to measures the strength of associations. The study identifies the prevalence of current tobacco use to be 14.1%, alcohol consumption behavior 38.3%, insufficient consumption of vegetables/fruits 64.1%, insufficient exercise 65.5% and exposure with secondhand smoke 55.8% and 47.1% at home and out of home respectively. The prevalence of the most common modifiable CVDs risk factor is insufficient exercise i.e. 65.5percent. There was significant association between current tobacco use and sex, marital status, and age. There was a significant association between fast food consumption behavior and sex of the participant. There was a significant association between obesity and age and sex. Females were likely to consume fast food and overweight. The study identifies a high prevalence of insufficient exercise, insufficient vegetable/fruit intake, alcohol consumption, tobacco use, daily fast food consumption and daily add salt on food. Community and school based intervention is needed to reduced the exposure to risk factors among 15-24years of age group.